Comparative transcriptomic study of matured fruit and post-fruit developmental stages in Malaysian durian varieties - Remmy Keong Bun Poh (Tanjung Malim, 2024)
Comparative transcriptomic study of matured fruit and post-fruit developmental stages in Malaysian durian varieties by Remmy Keong Bun Poh